Analisis Pengaruh Likuiditas, Solvabilitas, Aktivitas dan Profitabilitas Terhadap Kinerja Laporan Keuangan di Sektor Riteail pada PT. Sumber Alfaria Trijaya TBK - Devina Aulia Ramadhani; Nur inayah; Dita Anggraini; Nailah Arraswita; Yuni Artika Sari (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2025)
This is Many problems and difficulties impacted by PT. Acset Indonusa Tbk.'s performance in 2022 and 2023. With the use of liquidity, solvency, activity, and profitability criteria, this research aims to assess PT. Adhi Karya's financial performance from 2022 to 2023. A quantitative descriptive technique is used in this research methodology. This study's data is derived from the financial statement of PT. Acset Indonusa. With a cash management in 2022, this analysis predicts that PT. Acset Indonusa Tbk. would increase its liquidity and equity structure from 2022 to 2023. After experiencing setbacks in 2022, operational efficiency and aset pengelolaan improve in 2023. Profitability perseroan is also increasing, as seen by rising laba margins, ROI, and ROE, which also reduces rising kinerja keuangan and management.